LEARNING STRATEGIES USED BY A HIGH, A MIDDLE, AND A LOW ENGLISH ACHIEVERS: A CASE STUDY AT SMP N 2 WONOSARI KLATEN - SADONO , DANIAR SETIATI (2011)
DANIAR SETIATI SADONO. A 320070031. LEARNING STRATEGIES USED BY A HIGH, A MIDDLE, A LOW ENGLISH ACHIEVERS: A CASE xiv STUDY AT SMP N 2 WONOSARI KLATEN. Research Paper. Muhammadiyah University of Surakarta. 2011. This research aims at (1) describing the learning strategies used by a high, a middle, and a low English achievers at SMP N 2 Wonosari Klaten to improve their English ability, and (2) knowing the effects of various learning strategies used on the English achievement. The writer applies case study as the type of this research. She uses interview and observation for collecting the data. The data are taken from the subjects of the research in the form of field notes and interview scrip. The result of her research shows that the three subjects of this research use three kinds of learning strategy based on O'Malley and Chamot; metacognitive, cognitive, and social-affective in improving their English ability. The high achiever applies 17 learning strategies that consist of 7 metacognitive strategies, 8 cognitive strategies, and 2 social-affective strategies. The middle achiever employs 14 learning strategies that consist of 6 metacognitive strategies, 6 cognitive strategies, and 2 social-affective strategies. The low achiever uses 7 learning strategies that consist of 3metacognitive strategies, 2 cognitive strategies, and 2 social-affective strategies. The writer also shows that by using various learning strategies, the learners get some effects like getting the best score, being an effective student, and mastering English materials easily. The number of various learning strategies used by the English learner influences his/her achievement in improving English ability.